Reserva extrativista do Rio Cajari: verso e reverso da territorialização no sul do Amapá - Picanço, José Reinaldo Alves (2005)
The creation of Extractive Reserves (RESEX s) emerges from the resistence movement of the forest people and represents an alternative administration of the naturel resources in the from of Conservation Units (UC). From the institutional point of view the RESEX s are UC s of direct use belong of the Brazilian State, which concedes the right of use to resident families through a legal concession, uhich in based an the principle of coadministration between state and community. The use of these areas is based on the paradigm of sustainable development. In the Extractive Reserve of Rio Cajari over time there has been an experience of confliting interests between the big capital and the local population, which led to noticiable changes of lifestyle of the rural extrativist. In this sense the essay Extractive Reserve of Rio Cajari: various aspects of land use and awnership in southem Amapa , wants to analyse the nuances in which the land grabbing happened and how it affected the day to day of life its in habitants